Fazy przetwarzania informacji językowych w nauce obcojęzycznego słownictwa - Kubiczek, Agnieszka (Neofilolog, 2012)
In the article I am presenting the course of the process of learning vocabulary activated while teaching a foreign language. The paper takes the models of information processing and input processing as a starting point to describe the phases of vocabulary learning and to implicate the teaching procedures based on the insights in the natural processes of language acquisition. It provides theoretical background referring to the concept of instructed learning understood as the possibility of steering learners’ perception and processing of lexical structures by the teacher, and also examples on how to use this knowledge in the classroom.